Noble gas signatures of Antarctic nakhlites, Yamato (Y) 000593, Y000749, and Y000802 - Okazaki, Ryuji; Nagao, Keisuke; Imae, Naoya; Kojima, Hideyasu (National Institute of Polar Research, 2003)
P(論文) We have measured noble gases in three nakhlites from Antarctica, Yamato (Y) 000593, Y000749, and Y000802, by step-heating and total-melting methods.The trapped ^<36>Ar/^<84>Kr/^<132>Xe ratios determined for the bulk samples are around 80/3/1, identical to those of Nakhla. The Yamato nakhlites also release noble gases showing high ^<129>Xe/^<132>Xe (up to 1.486) and low ^<84>Kr/^<132>Xe (～1.5) at 1000 and 1300 ℃, which is one of the most characteristic signatures of nakhlites. The low ^<84>Kr/^<132>Xe, as compared to that of the Mars atmosphere, suggests the presence of a fractionated Martian atmosphere.Cosmic-ray exposure ages based on cosmogenic ^<21>Ne are 11.7, 11.9, and 13.0 Ma for Y000593, Y000749, and Y000802, respectively. This supports the pairing based on the mineralogical and petrographical similarities and the location of the finds. The average of the ^<21>Ne exposure ages is 12.05±0.69 Ma. We also calculated an apparent ^<81>Kr-Kr age as 11.8±1.0 Ma from cosmic-ray produced radioactive ^<81>Kr and stable Kr isotopes from Y000593. The coincidence with the ^<21>Ne exposure age indicates a short terrestrial age (<0.04 Ma). Hence, the Mars ejection time, as calculated from the sum of the ^<21>Ne exposure age and terrestrial age, is 12.1±0.7 Ma. Calculated K-Ar gas retention age for the Yamato nakhlites is 1.24±0.22 Ga. The ejection time and gas retention age are close to those of non-Antarctic nakhlites and Chassigny. This suggests that the Yamato nakhlites were ejected from Mars together with other nakhlites and Chassigny. Xenon isotopes are mixtures of Chassigny Xe, fission Xe, and the Mars atmosphere. High-temperature fractions (1000-1750℃) are enriched in the Mars atmosphere and fission Xe components, compared to lower temperature fractions. There are similarities in Xe isotopes between Y000749 and Y000802 showing excesses in ^<129>Xe and ^<136>Xe, whereas Y000593 has only small excesses. ...